2014
DOI: 10.1002/cmdc.201300533
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Functional and Structural Properties of 3‐Arylcoumarin as an Interesting Scaffold in Monoamine Oxidase B Inhibition

Abstract: The design, synthesis, pharmacological evaluation, and theoretical studies of a new series of halogenated 3-arylcoumarins were carried out with the aim of finding new structural and biological features. This series displays several alkyl, hydroxy, halogen, and/or alkoxy groups in both benzene rings of the 3-arylcoumarin scaffold. Most of the compounds studied show high affinity and selectivity for the human monoamine oxidase B (hMAO-B) isoenzyme, with IC50 values in the low nanomolar and picomolar range. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…[19] 3-(3'-Bromophenyl)-6-(2-oxopropoxy)coumarin (4): White solid (80 mg, yield: 83 %): mp: 167-168 8C. [19] General procedure for the synthesis of 6-acetoxy-3-arylcoumarins (6-9): Compounds 6-9 were synthesized under anhydrous conditions, using material previously dried at 60 8C for at least 12 h and at 300 8C during the few minutes immediately prior to use. A solution containing anhydrous CH 3 CO 2 K (2.94 mmol), the phenylacetic acid derivative (1.67 mmol), and the 2,5-dihydroxybenzaldehyde (1.67 mmol) in Ac 2 O (1.2 mL) was held at reflux for 20 h. The reaction mixture was cooled, neutralized with 10 % aqueous NaHCO 3 , and extracted (3 30 mL) with EtOAc.…”
Section: Chemistrymentioning
confidence: 97%
See 2 more Smart Citations
“…[19] 3-(3'-Bromophenyl)-6-(2-oxopropoxy)coumarin (4): White solid (80 mg, yield: 83 %): mp: 167-168 8C. [19] General procedure for the synthesis of 6-acetoxy-3-arylcoumarins (6-9): Compounds 6-9 were synthesized under anhydrous conditions, using material previously dried at 60 8C for at least 12 h and at 300 8C during the few minutes immediately prior to use. A solution containing anhydrous CH 3 CO 2 K (2.94 mmol), the phenylacetic acid derivative (1.67 mmol), and the 2,5-dihydroxybenzaldehyde (1.67 mmol) in Ac 2 O (1.2 mL) was held at reflux for 20 h. The reaction mixture was cooled, neutralized with 10 % aqueous NaHCO 3 , and extracted (3 30 mL) with EtOAc.…”
Section: Chemistrymentioning
confidence: 97%
“…[15] 3-(3'-Methylphenyl)-6-(2-oxopropoxy)coumarin (2) 3-(4'-Bromophenyl)-6-(2-oxopropoxy)coumarin (3): White solid (80 mg, yield: 81 %): mp: 157-158 8C. [19] 3-(3'-Bromophenyl)-6-(2-oxopropoxy)coumarin (4): White solid (80 mg, yield: 83 %): mp: 167-168 8C. [19] General procedure for the synthesis of 6-acetoxy-3-arylcoumarins (6-9): Compounds 6-9 were synthesized under anhydrous conditions, using material previously dried at 60 8C for at least 12 h and at 300 8C during the few minutes immediately prior to use.…”
Section: Chemistrymentioning
confidence: 98%
See 1 more Smart Citation
“…Different research groups, including ours, have shown that coumarin is a privileged scaffold for the rational discovery and development of new h MAO‐B inhibitors (Figure ) and antioxidant agents . In addition to being very potent and selective MAO inhibitors, several leads previously reported by the group have proven to be reversible inhibitors . Moreover, hybrid molecules bearing the coumarin scaffold have been already reported by the group .…”
Section: Introductionmentioning
confidence: 84%
“…[15][16][17] In addition to being very potent and selective MAO inhibitors, several leads previously reported by the group have proven to be reversible inhibitors. [18][19][20] Moreover, hybrid molecules bearing the coumarin scaffold have been already reported by the group. [21,22] Therefore, the development of coumarin-rasagiline hybrids, and the methodology and results described in this manuscript, may contribute to a global effort to find efficient molecules as future perspectives for the treatment of Parkinson's disease (Figure 1).…”
Section: Introductionmentioning
confidence: 99%